Evaluation of a fluorescent dye to visualize touch DNA on various substrates. Issue 4 (24th February 2021) - Champion, Jessica; Kanokwongnuwut, Piyamas; van Oorschot, Roland A. H.; Taylor, Duncan; Linacre, Adrian
Abstract: A wide variety of items are submitted as evidence in a forensic investigation. Identifying the location of DNA on such items is central to maximizing DNA profiling success and thus the ability to link a person of interest to a particular item or crime. Recent publications describe a fluorescent staining method using Diamond™ Dye (DD) to visualize cellular material on the surface of non‐porous items (e.g., glass, plastic). However, substrates of varying porosity and background color have not yet been examined. Varying porous substrates (i.e., paper bank note, stamp, cigarette, wooden matchstick, and fabric) and non‐porous substrates (i.e., enamel tooth and plastic bank note) were examined for their suitability with the use of DD. To improve the visualization of cellular material on the porous substrates, we also explored two DD diluents and adjusting image contrast. The results suggest the optimal diluent depends on the absorbent nature of the substrate. For example, ethanol was sufficient for visualization on the non‐porous substrates, whereas water was better for the porous substrates. While cellular material was detected on the paper bank note, tooth, and stamp, background fluorescence or autofluorescence and surface type of matchstick prevented clear visualization on this substrate. It was also determined that by adjusting the contrast of images for tooth, paper bank note and matchstick aided in the detection of cellular material. Overall, this study extends the use of DD for latent DNA detection to absorbent substrates, highlights the limitations associated with these substrate types, and suggests modifications to improve visualization on these challenging substrates.